Modeling of the habitat suitability of European sprat (Sprattus sprattus, L.) in the Adriatic Sea under several climate change scenarios - Palermino, Antonio; De Felice, Andrea; Canduci, Giovanni; Biagiotti, Ilaria; Costantini, Ilaria; Centurelli, Michele; Menicucci, Samuele; Gašparević, Denis; Tičina, Vjekoslav; Leonori, Iole (Frontiers in Marine Science, 2024)
The Mediterranean Sea represents the lower latitudinal limit of European sprat' range, where it is considered a sentinel species favouring temperate-cold temperatures. Sprattus sprattus is a plankton feeder which plays an important ecological role in contributing to the transfer of energy from lower to higher trophic level, but climate-driven increases in sea temperatures may reduce the suitability of the pelagic habitat and threaten the tropho-dynamic role of sprat in areas such as the Adriatic Sea. The latter is an enclosed basin characterized by shallow waters and high annual temperature variation. Here, to investigate present and future habitat suitability areas for sprat, we applied four species distribution models (SDMs) using fishery-independent data collected from 2004 to 2021, along with remotely sensed and modelled environmental variables. A set of nine environmental predictors was tested, and the resulting best model was averaged in an ensemble model approach. The best ensemble models revealed a good to high accuracy (sensitivity and specificity ≥ 0.8). The sea surface temperature and chlorophyll concentration emerged as the main explanatory variables in predicting the potential habitat of sprat, followed by bathymetry. The resulting probability of occurrence maps revealed that the species is bounded in the northern Adriatic Sea, where a longitudinal shift of high-suitability habitats from inshore to deeper and colder waters was detected between early and late summer. Future projections under IPCC Representative Concentration Pathway (RCP) scenarios 4.5 (intermediate emission) and 8.5 (high emission-warm) underline small changes along with a gain of new areas in late summer in the short-term period (up to 2050). Conversely, the temperature increase projected for the end of the century is predicted to cause a loss of suitabileity habitat area for sprat up to 88% under high emission-warm scenario relative to current habitat occupancy throughout the basin.